Decolonising the Curriculum: Perspectives of Indonesian Academics with Overseas Qualifications - Ririn Syahriani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study explores how Indonesian academics with overseas educational backgrounds interpret and enact curriculum decolonisation in higher education. Although decolonisation has gained increasing attention globally, it is often reduced to symbolic inclusion rather than substantive epistemic transformation. Using a qualitative design, data were collected through an online open-ended questionnaire involving ten Indonesian lecturers who completed postgraduate studies abroad. Thematic analysis generated four interconnected themes: recognising the colonial legacy embedded in university curricula, pursuing epistemic justice through the inclusion of local knowledge systems, negotiating transnational positionalities shaped by both global and local academic experiences, and engaging in the ongoing process of decolonising the self. The findings suggest that participants viewed curriculum decolonisation not as the rejection of Western knowledge but as a critical effort to create more equitable and contextually relevant knowledge practices. However, their efforts were frequently constrained by institutional pressures associated with internationalisation, publication metrics, and global ranking systems that continue to privilege Eurocentric epistemologies. The study concludes that meaningful curriculum decolonisation in Indonesia requires both individual reflexivity and broader structural transformation to support epistemic plurality within higher education.